Pensions: five key decisions for the next government - Jonathan Cribb; Heidi Karjalainen; Laurence O'Brien (Institute for Fiscal Studies (IFS), 2024)
The current generation of pensioners has, in general, been better served by the UK's mix of state and private pension provision than earlier generations were. Pensioners today have disposable incomes - once you take account of housing costs and children - that on average are similar to those below pension age, as well as lower poverty rates. The risk is that this has led policymakers and commentators to take their eye off the pensions ball. Just because the current generation of pensioners is doing better, that does not mean that will continue for future generations. There remain challenges that need addressing. The next government needs to take decisions on pensions which are not made easier by the pressures that an ageing population puts on the public finances. In this report we identify five key priorities for whoever is pensions minister after the general election. Some of these issues need decisions soon. A failure to address others would risk storing up greater problems for the future. Underlying many of the challenges facing many saving for retirement today is a lack of risk sharing. Automatic enrolment into workplace pensions has been a big policy success. But individual bad luck or bad decisions - or a failure to make a decision - can still have significant consequences in a way which was much less true for those who enjoyed old-style defined benefit pensions, benefited from state earnings related pensions, or had no choice but to annuitise their defined contribution pension pot.
Keywords: 330; Government finances and spending; Savings; pensions and wealth; Ageing; Benefits; Distributional effects; Government spending; Living standards; Pensioner benefits; Private pensions; Public finance; Savings; State pensions; Working age benefits